Enhanced sensor life using UV treatment of sulphur poisoned Pt-PtOx. (April 2019) - Benedict, Samatha; Bhat, Navakanta
Graphical abstract: Highlights: Core-shell Pt-PtOx nanowire is developed using oxygen plasma of Pt nanowire. To achieve higher fabrication yield of nanowire, oxidation conditions are optimized. Fabricated sensor shows response of 6.4% (1 ppm) H2 S at 150 °C with LOD of 10 ppb. Sensor surface is poisoned on exposure to 3 ppm H2 S at 150 °C due to formation of PtS. UV irradiation at 248 nm wavelength for 5 min results in sensor response recovery. Abstract: In this work, we report a novel method for recovery of sulphur poisoned platinum/platinum oxide (Pt-PtOx ) core-shell nanowire sensor using UV irradiation.The optimum core to shell thickness ratio and the operating conditions are the key factors to achieve a high-performance H2 S sensor, described in this report.The fabricated core-shell nanowire sensor demonstrated response of 6.4% at 1 ppm H2 S with detection limit of 10 ppb at 150 °C operating temperature. The sensor undergoes prominent time-dependent poisoning at H2 S exposure of 3 ppm when operated at 150 °C due to sensor surface contamination by sulphur, later confirmed by XPS analysis. Ultraviolet light at two wavelengths, 365 nm, and 248 nm is investigated to recover the poisoned Pt-PtOx surface.UV irradiation at 248 nm for 5 min results in sensor recovery, confirmed by further H2 S sensing characterization and XPS studies on the recovered sensor. To the best of our knowledge, this is one of the first reports on UV irradiation for recovery of sulphur poisoned metal-oxide surfaces.